Comparison of athletic performance of Turkish ice hockey players with ACE I/D (rs1799752), ACTN3 (rs1815739), PPARA (rs4253778) and HIF1A (rs11549465) polymorphisms: Athletic performance and genetic in Turkish ice hockey athletes - Doğan, Canan Sercan; Akkoc, Orkun; Özağır, Meltem; Avci, Sinan; Biçer Baikoglu, Selin; Kurudirek, Muhammet İrfan; Ulucan, Korkut (Cellular and Molecular Biology, 2024)
Our study is aimed at examining the Ice Hockey National Team players with regard to ACE I/D (rs1799752), ACTN3 (rs1815739), PPARA (rs4253778) and HIF1A (rs11549465) polymorphisms and physical tests. This study was participated by 21 players from ice hockey national team. While ACE I/D (rs1799752) polymorphism was obtained using conventional polymerase chain reaction method (PCR), ACTN3 (rs1815739), PPARA (rs4253778) and HIF1A (rs11549465) polymorphisms were produced by real time polymerase chain reaction method (qPCR). Athletic performance analysis, on the other hand, was based on the assessment of maximal oxygen consumption capacity (VO2max), anaerobic performance, flexibility and strength tests. In our cohort, ACE I/D (rs1799752) polymorphism was determined as 24% genotype II, 33% genotype ID, and 43% genotype DD. ACTN3 (rs1815739) polymorphism was determined as 24% genotype RR, 43% genotype RX, and 33% genotype XX. PPARA (rs4253778) polymorphism was observed as 71% genotype GG, 14.5% genotype GC, 14.5% genotype CC. HIF1A (rs11549465) polymorphism was found to be 67% genotype CC, 33% genotype CT. Concerning physical tests, the evaluation of flexibility test results among genotype groups did not yield significant differences (p=0.365). No significant difference was found among genotype groups with respect to leg strength test results (p=0.691). The evaluation of handgrip strength test results among genotype groups did not reveal significant differences (p=0.679). No significant differences were found among genotype groups when VO2 max test results were examined (p=0.686). A significant relationship was found in the speed test and HIF1A rs11549465 polymorphism evaluation (p = 0.008). No significant results were detected when comparing the speed test with other polymorphisms (p = 0.65). The results of our study support the previous studies which had focused on the potential relation between the relevant gene polymorphisms and athletic performance of ice hockey players. However, doing further studies with larger cohorts is recommended in order to understand the relationship between the relevant polymorphisms and athletic performance of ice hockey players.